(3OjhGf GdeGQOjfjs - (3eMeO Hf CHj HcQ Hf TQa GdeGQOGfj, YdGA GdOjfs
(3ChdgG (B:s
(3hHYO(B: (3aEffj cfJ aj ZQg GdTHGH dgLG Hafhf GdBOGH Ke deG QCjJ GdReGf aj ZGjI GdaSGO cCqf Hg fbUkG hChd GdehLhO efg s
(3BNQgG (B:s
(3EPG CTQbJ CfhGQ TeS LeGdg afLe GdCYGOj NjaI efg Cbd s
(3ZjQ eQJH Ydi GdMQhas
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B189 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs